An outcome analysis of children who underwent repair of spinal dysraphism Hospital Universiti Sains Malaysia - Badrisyah, Idris (2008)
An outcome analysis of children who underwent spinal dysraphism repair in Hospital Universiti Sains Malaysia. Objective: To evaluate the impact of multiple factors and outcome (ambulatory function, and control of bowel and bladder) associated with spinal dysraphism following surgical repair. Methodology: A retrospective chart review of children operated for spinal dysraphism in Hospital Universiti Sains Malaysia from 1 January 1990 to 31 December 2004 was conducted. Children who were solely operated before age 12 years old and who had been followed-up for at least 18 months post repair were included in the study. Results: A total of 53 children with spinal dysraphism were included in the study. Open spinal dyraphism was 79.2% and closed spinal dysraphism 20.8%. 77.4% of patients with spinal dysraphism were ambulatory after two years following repair. Univariate analysis of the association of predictors with ambulatory status revealed that hydrocephalus, presence of shunt, motor and reflex score of SBNS, and status of difference between functional and anatomical level were significant factors of ambulatory status. By using multiple logistic regression, none of the significant predictors from the univariate analysis for ambulation function remained significant. The significant predictors from the univariate analysis of poor bladder control in this study were related to the type of spina bifida, presence of hydrocephalus, presence of sensation at 81 and below, and functional level below LS and above. From multivariate analysis, type of spinal dysraphism and functional level at L5 were found to be the significant predictors for poor bladder control. Conclusion: Open spinal dysraphism was the more common operated spinal dysraphism in Hospital Universiti Sains Malaysia. This study has demonstrated various factors that can affect the ambulatory function, and control of bowel and bladder in children with spinal dysraphism.